2021
DOI: 10.3389/fnut.2021.734620
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Bacterial Cellulose Nanofibers/Soy Protein Isolate Colloidal Particles for the Stabilization of High Internal Phase Pickering Emulsions by Anti-solvent Precipitation and Their Application in the Delivery of Curcumin

Abstract: In this study, the anti-solvent precipitation and a simple complex method were applied for the preparation of bacterial cellulose nanofiber/soy protein isolate (BCNs/SPI) colloidal particles. Fourier transform IR (FT-IR) showed that hydrogen bonds generated in BCNs/SPI colloidal particles via the anti-solvent precipitation were stronger than those generated in BCNs/SPI colloidal particles self-assembled by a simple complex method. Meanwhile, the crystallinity, thermal stability, and contact angle of BCNs/SPI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In humans, oral administration of CUR at a dose of 2 g resulted in undetectable or extremely low serum levels ( 6 ). An array of carriers has been proposed to help overcome one or more of these shortcomings, and thus improve the efficacy of CUR in various disease models ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, oral administration of CUR at a dose of 2 g resulted in undetectable or extremely low serum levels ( 6 ). An array of carriers has been proposed to help overcome one or more of these shortcomings, and thus improve the efficacy of CUR in various disease models ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The flocculation degree of divalent and trivalent metal ions is more than approximately 10–100 times that of univalent metal ions at the same ionic strength ( 47 ). Within a certain range, improving ionic strength can increase the hydrophobicity of particles to promote the adsorption of particles at the oil and water interface ( 48 ). An appropriate amount of ionic strength can also reduce the electrostatic repulsion between particles, which is conducive to the accumulation of particles at the surface of emulsion droplets to form a layer ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Self-assembled composite particles are significantly affected by the type of particles, concentration, dissolution temperature, pH, ionic strength, and the self-assembly methods [ 51 , 52 ]. Shen et al [ 53 ] used the anti-solvent method with simple complexation to prepare protein–polysaccharide composite particles. Additionally, it was found that the particles prepared by the anti-solvent method had better protein conformation, surface activity, and gel strength, and the HIPPE stabilized with the anti-solvent composite particles had good droplet size, crystallinity, and thermal stability.…”
Section: Hippe Stabilized By Solid Particlementioning
confidence: 99%
“…In the process of emulsion preparation, solid particles are wetted by both oil and water phases; the wettability of the particles is an important property to evaluate the emulsification ability of solid particles for HIPPE as well as the stability of the emulsion [ 53 ]. The wettability of the particles reflects their degree of hydrophilicity and hydrophobicity; only solid particles with dual wettability can be used as stabilizers for HIPPE.…”
Section: Hippe Stability Mechanismmentioning
confidence: 99%